2018
DOI: 10.1097/sla.0000000000002190
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Minimally Invasive Surgery for Local Excision of Benign and Malignant Rectal Neoplasia

Abstract: For carefully selected patients, TAMIS for local excision of rectal neoplasia is a valid option with low morbidity that maintains the advantages of organ preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
76
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 48 publications
1
76
1
Order By: Relevance
“…and Lee et al . report outpatient surgery in 80% and 76% of their TEM/TAMIS patients, respectively . While Lee et al .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…and Lee et al . report outpatient surgery in 80% and 76% of their TEM/TAMIS patients, respectively . While Lee et al .…”
Section: Resultsmentioning
confidence: 98%
“…A survey of recent publications suggests that admission to hospital is still common, with most series reporting a minimum hospital stay of of 1 day (see Table 4) [10][11][12][13][14]18,19]. However, Laliberte et al and Lee et al report outpatient surgery in 80% and 76% of their TEM/TAMIS patients, respectively [4,6]. While Lee et al do not report readmission, Laliberte et al observed a readmission rate of 8.6% in the day-care TEM patients, which is similar to our experience.…”
Section: O312mentioning
confidence: 99%
“…It may help to identify resection margins in surgery for hepatocellular carcinoma. Methylene blue has been used to treat cyanide poisoning and drug-induced methaemoglobinaemia [1][2][3][4].…”
mentioning
confidence: 99%
“…Rare but severe reactions include seizures, prolonged disorientation, toxic metabolite encephalopathy, blistering at the pulse oximetry probe site and serotonin toxicity. However, these complications occur with high doses or intravenous use [1]. The US Food and Drug Administration has warned of possible central nervous system reactions in patients undergoing parathyroid surgery who are also taking serotonergic agents.…”
mentioning
confidence: 99%
“…Transanal minimally invasive surgery (TAMIS) is a safe and effective method for the local excision of benign neoplasms of the mid and distal rectum . Submucosal injection of normal saline may improve the safety of polypectomy by elevating the polyp and reducing the risk of a deep intramural burn and perforation.…”
mentioning
confidence: 99%